To Be or Not to Be Natural: Clichés of Emotion in Screen Translation - Santiago Araújo, Vera Lúcia (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2004)
AbstractThe objective of this article is to report the results of my Doctoral thesis that investigated the translation of American English clichés into Brazilian Portuguese in five dubbed and subtitled films. Clichés, also called situational or routine formulas, are those expressions used by speakers of a certain language which have become stereotyped and commonplace due to repetitive use. More than 250 clichés expressing emotion were found in the corpus. The study aimed at the description of the norms that regulated Brazilian translators’ rendering of the clichés. The analysis revealed that one norm governed the translation, that of absence of naturalness. That is, the translator sometimes chose an expression which is not natural in Portuguese. This was mainly due to the constraints of the audiovisual setting and the translator’s wish to produce a ‘faithful’ translation.